Tubercular dactylitis with discharging sinuses: A very rare presentation of skeletal tuberculosis - Alakes Kumar Kole (Annals of Medical Science and Research)
Skeletal tuberculosis is a common form after pulmonary and lymphnode involvement, but involvement of soft tissues is rarely seen after pediatric population. Tubercular dactylitis is such a lesion and needs consideration before ordering more costly investigations.